2017
DOI: 10.12691/jfnr-5-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound Pretreatment and Ageing Processing on Quality and Tenderness of Pork Loin

Abstract: Tenderness is a primary indicator of meat quality, which directly influences consumer acceptance of the meat. Ultrasound can effectively increase the tenderness of red meat, such as pork and beef, by breaking up muscle fibers and connective tissues through mechanical force, thus making it a basis for physical tenderization of meat to improve meat quality. In this study, ultrasound (2200 W, 15 kHz) was applied in the processing of pork loin to explore the influences of varying treatment durations (0-6 minutes) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
(89 reference statements)
0
26
0
Order By: Relevance
“…As for fresh meat, ultrasonic treatment with a frequency of 25 kHz and an intensity of 2 W cm −2 was applied in semimembranosus muscles resulting in tender meat during aging (Dickens et al ., ). Ultrasound (2200 W, 15 kHz) could effectively tenderize the pork loin and decrease shear force by 72.3% after 48 h aging (Yeung & Huang, ). It was reported that beef M. semitendinosus treated by ultrasound of 20 kHz could significantly increase myofibrillar fragmentation index (MFI) and decrease Warner‐Bratzler shear force (WBSF) (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…As for fresh meat, ultrasonic treatment with a frequency of 25 kHz and an intensity of 2 W cm −2 was applied in semimembranosus muscles resulting in tender meat during aging (Dickens et al ., ). Ultrasound (2200 W, 15 kHz) could effectively tenderize the pork loin and decrease shear force by 72.3% after 48 h aging (Yeung & Huang, ). It was reported that beef M. semitendinosus treated by ultrasound of 20 kHz could significantly increase myofibrillar fragmentation index (MFI) and decrease Warner‐Bratzler shear force (WBSF) (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, 15 min of US37 pre-treatment had no negative effects on hardness compared to control samples (p > 0.05). In a study by Yeung and Huang [41] , the hardness of ultrasound pre-treated pork loins determined by texture profile analysis was reported to decrease while overall acceptance scores of pork loins increased.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more advanced techniques are used to combine ageing or other interventions to make the best use of the combined tenderising effects. For instance, ultrasound-assisted ageing can increase muscle pH (neutral pH) to induce higher calpain activity and intervene the early glycolysis of ageing by damaging the cell structures and changing protein conformation (Got et al 1999;Yeung & Huang 2017). Moreover, the μ-calpain in neutral pH muscle displays sufficient proteolytic activity to degrade MP and regulate some structural proteins during the ageing for acceptable tenderness (Kim et al 2008;.…”
Section: Combination Techniquesmentioning
confidence: 99%